(untitled) (Global Journal of Human-Social Science, 2014)
The Holy Quran is a book that explains the phenomenon of fate which is hidden beneath the physical event and enables us to realize the cause of the disaster and uncover them. It is said in the Qur’an " Corruption h as appeared throughout the land and sea by (reason of) what the hands of people have earned." We understand under the light of this verse that the tsunamis, floods and storms which destroy cities and settlements are a result of deterioration caused by human hands in land and seas. With this statement Qur’an point out a universal law in the universe and who acts opposite to it will h ave an equal pain. For this reason Qur’an and hadiths ordered us to treat our environment delicately and sensitively. Those who not have any awareness of these fact will be punish in the world and hereafter. So the article is looking at the problem of environmental pollution from the perspective of fate.